High bar swing performance in novice adults: Effects of practice and talent - Busquets, A.; Marina, M.; Inurtia, A.; Ranz, D.; Angulo-Barroso, R. M. (Research Quarterly for Exercise and Sport, 2011)
An individual's a priori talent can affect movement performance during learning. Also, task requirements and motor-perceptual factors are critical to the learning process. This study describes changes in high bar swing performance after a 2-month practice period. Twenty-five novice participants were divided by a priori talent level (spontaneous-talented [ST] and nonspontaneous-talented [NST]) and compared to experienced gymnasts. Additionally, we assessed their perception of their performance level before and after practice. We defined three events independently for hip (H) and shoulder (S) angle joints and for the lag between consecutive events (phases [P]): the smallest angle during downswing (P1H, P1S), the largest angle after P1 (P2H, P2S), and the smaller angle during upswing (P3H, P3S). Movement performance variables were the maximum elevation on the downswing (Pi) and the upswing (Pf), and the total path between both (swing amplitude). Data were collected during pre- and postpractice sessions by two video cameras. At the end of both sessions, participants drew a sketch to represent their perception of their performance level relative to the Pi, Pf, and the hip events. Results showed a similar practice effect in the swing amplitude in both novice groups. However, the ST group's performance and perception variables on the downswing improved more than the NST group due to practice. This study suggests that (a) downswing improvements were easier than in the upswing, possibly due to familiarity of the visual reference in combination with proprioceptive feedback; and (b) being ST may involve a better or faster gain in perception of self-action compared to NST.